Ciclo Ruta Turística para la Parroquia El Arenal, Cantón Puyango, Provincia de Loja” - Córdova Ureña, Sandra Pamela (2018)
El Arenal parish is geographically located in the center of Puyango canton, province of Loja. The parish El Arenal has a great tourist potential to be a spa of sulphurous waters of volcanic origin, in the same way this parish drives tourism through entrepreneurship, its people making crafts of bamboo cane, the undertakings of artisan panela and honey of catana The present title work called "Cycle tourist route for the parish of El Arenal, canton Puyango, province of Loja." Aims to generate tourism spaces to contribute to local development, generating sources of income, and at the same time raise awareness and integrate its main tourist attractions. In addition, it is proposed to establish tourist signage, in order to facilitate the location and make pleasant the visit of tourists who arrive at the parish. In order to comply with the present investigation, the general objective was "To elaborate a tourist route cycle for the parish of El Arenal, Puyango canton, province of Loja". For the development of this general objective, the following specific objectives were established: The first objective "To carry out the tourist diagnosis of the parish of El Arenal, Puyango canton, Loja province", the analytical and synthetic method was used, taking as reference the tourist diagnostic matrix of Carla Ricaurte, adapting it to gather information from the parish as of the different attractions through the tourist inventory cards of the Ministry of Tourism. In the same way, a SWOT matrix was elaborated that allowed the identification of the strengths, opportunities, weaknesses and threats; useful information for the approach of strategies to improve the tourist product. For the development of the second objective "Propose the design of a cycle route for the parish of El Arenal, Puyango canton, province of Loja", the inductive and deductive method was applied. In order to achieve this objective, maps were made where the route will be established, along with the signage that will be located at key points in order to easily reach the attractions. In addition, a brand of the cycle route was developed so that it can be promoted. For the fulfillment of the third objective "Socialize the results of the research work with the social actors involved" the necessary steps were taken to bring together the main actors of the parish using the method of rapid analysis and participatory planning MARPP, with the purpose to carry out the socialization of the proposal to let the parish know how it will develop and have the opportunity to contribute with their ideas to improve the tourism product. 5 As suggested recommendations of the present work, it is established the generation of a cycle route that has the necessary signage for the identification of tourist attractions. It is concluded that the objectives set out in the current research, was complemented according to the established, resulting in a tourist cyclist route, which can be for future research, as well as for the Gad of El Arenal parish. and in this way promote a route that has the necessary characteristics to receive tourists arriving at the parish, through the promotion and dissemination that is established as a proposal and the necessary signage for tourists to guide.